Sharing lessons learned from COVID-19 vaccine introductions: a global community forum for countries - Walldorf, Jenny Anne; Chiu De Vazquez, Cindy; Barbosa De Lima, Ana Carolina; Struminger, Bruce; Groom, Amy; Burke, Lauren; Mayigane, Landry Ndriko; Chang Blanc, Diana; Vedrasco, Liviu (Frontiers in Public Health, 2024)
To optimize the efficient introduction and deployment of COVID-19 vaccines across the globe during the COVID-19 pandemic, in April 2021 WHO launched a new process and tools for countries to rapidly review the early phase of countries’ COVID-19 vaccine introduction. This methodology is called the COVID-19 vaccination intra-action review, also known as mini COVID-19 vaccine post-introduction evaluation (mini-cPIE). As of November 2022, 46 mini-cPIEs had been conducted. In collaboration with Project ECHO, WHO convened and facilitated real-time experience sharing and peer-learning among countries following their mini-cPIEs through a virtual global real-time learning forum. This five-session clinic series was attended by 736 participants from 129 countries. Based on post-session feedback surveys, when asked about the utility of the sessions, half of the participants said that sessions led them to review national guidelines and protocols or make other changes to their health systems. The post-series survey sent following the end of the clinic series showed that at least eight countries subsequently conducted a mini-cPIE after participating in the clinics, and participants from at least nine countries indicated the experience shared by peer countries on the clinic largely benefited their COVID-19 vaccine introduction and deployment. In this article, we highlight the benefits and importance of creating a global experience-sharing forum for countries to connect and share pertinent learnings in real-time during an international public health emergency. Moving forward, it is critical to foster a culture of individual and collective learning within and between countries during public health emergencies, with WHO playing an important convening role.